Marriage Agreements Made in the Time of Marriage and Its Legal Consequences on Third Parties and Minangkabau Traditional Law after the Constitutional Court's Decision Number 69/PUU-XIII/2015 Comes Into Force - Firdaus Arifin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The marriage agreement is regulated in Article 29 of Law Number 1 of 1974 concerning Marriage which essentially states that a marriage agreement must be made with a notarial deed, or with a written agreement ratified by the Marriage Registrar, before the marriage takes place or at the time the marriage takes place and The Marriage Agreement shall come into force since the marriage was held, and cannot be changed, unless from both parties there is an agreement to change and the change does not harm a third party. Based on the Decision of the Constitutional Court Number 69/PUU-XIII/2015, the Court is of the opinion that the implementation of the marriage agreement is not limited to being carried out only at or before the marriage is held, but also during the marriage contract, the marriage agreement can be executed by husband and wife upon mutual agreement.